inhibitory effect of vinegar and its mixture with honey on some pathogenic bacteria - Bushra Dallee Hamad (College of Education for Pure Sciences, 2010)
Abstract This research aim to study antibacterial activity of vinegar only and a mixture of vinegar and honey against some pathogenic bacteria. The results showed that mixture of vinegar and honey was more active than the vinegar only, and it was found that there were differences in sensitivity of studied bacteria towards that different lightening. Staphylococcus epidermidis was the most sensitive to both concentrated 50/50, 25/75 it was shown the superiority of that mixture of vinegar and honey activity upon some of those antibiotics according to the type of studied bacteria, which may indicate the capability of using this mixture of vinegar and honey to control pathogens which are sensitive to it.